PRODUCTIVITY OF WHITE SHRIMP (Litopenaeus vannamei) WITH THE ADDITION OF PROBIOTICS AND PREBIOTICS - Andina Chairun Nisa; Diklawati Jatayu; Komang Aditya Pratama (Jurnal Perikanan Unram, 2024)
Vaname shrimp remains a prime commodity due to several advantages, including the ability to thrive in a salinity range of 0.5-31 ppt, with a stocking density of 100-300 individuals/m², a faster growth cycle of 90-100 days, and a high appetite leading to rapid growth. Currently, the technology for culturing vaname shrimp has advanced with the implementation of intensive systems that utilize high stocking densities, although this impacts water quality. One approach to maintaining good water quality, especially in reducing organic waste, is the use of prebiotics and probiotics. Further studies are needed to determine the productivity of vaname shrimp with the addition of probiotics and prebiotics in shrimp culture. This research employed a survey method with parameters observed including productivity and water quality. Productivity encompassed stocking density, Average Body Weight (ABW), Average Daily Growth (ADG), population, biomass, Food Conversion Rate (FCR), Survival Rate (SR), and size. Water quality parameters measured included salinity, temperature, pH, DO using a Multitester, alkalinity, TOM, Ca, Mg, Total Hardness using titration, PO4, NH4, NO3, NO2 using a test kit, the number of green algae, blue-green algae, diatoms, euglena, and dinoflagellates using a hemocytometer, zooplankton, and protozoa using a Sedgewick Rafter, total bacteria, total vibrio, and the number of yellow, green, and black vibrio using Total Plate Count (TPC). Data analysis used descriptive methods. The results showed that the harvest exceeded the company's target, and the SR and FCR values were categorized as good in vaname shrimp cultivation. Water quality measurements indicated that conditions were still optimal for vaname shrimp culture.